QUANTIFICATION OF BILASTINE AND MONTELUKAST COMBINATION IN FORMULATIONS UTILIZING LIQUID CHROMATOGRAPHY: STABILITY STUDIES - VIJAYALAKSHMI, KANCHARLA; ANAND ANDREWS, BETHAPUDI SAMUEL; NAGESWARA RAO, BOLINENI (International Journal of Applied Pharmaceutics, 2021)
Objective: We have developed a “stability-indicating RP-HPLC” procedure for the Bilastine (BLS) and montelukast (MTL) analysis of tablets. Methods: The quantification of BLS and MTL combination was implemented utilising a Waters column (C18, 5 μm, 250 mm and 4.6 mm). Isocratic mobile phase had 60% volume KH2PO4 of 0.1M strength with pH 4.2 units and 40% volume methanol at a flow with 1.0 ml/min speed. UV detection at 232 nm was done to examine BLS and MTL. Stability experiments of BLS and MTL under distinctive environments of stress were also performed. Results: The BLS and MTL were eluted at 1.810 min and 2.551 min, respectively. The responses were found to be linear for the concentration ranges of 10-30 µg/ml (BLS) and 5-15 µg/ml (MTL). Percent comparative standard deviance for precision was 0.331% (BLS) and 0.486% (MTL). Percent assay for accuracy was 98.96% (BLS) and 99.00% (MTL). The detection limit and quantitation limit measures for BLS were 0.018 µg/ml and 0.059 µg/ml, respectively, while for MTL it was 0.024 µg/ml and 0.081 µg/ml, respectively. Robustness studies authorized that the method is robust with percent comparative standard deviance of a highest 1.950%. Conclusion: The developed “stability-indicating RP-HPLC” procedure for the BLS and MTL analysis is simple, sensitive, precise, specific and robust, making it appropriate to the assessment of BLS and MTL in a tablet formulation.